Transplantation of 3D MSC/HUVEC spheroids with neuroprotective and proangiogenic potentials ameliorates ischemic stroke brain injury. (May 2021) - Hsu, Ting-Wei; Lu, Yu-Jen; Lin, Yu-Jie; Huang, Yu-Ting; Hsieh, Li-Hung; Wu, Bing-Huan; Lin, Yu-Chun; Chen, Li-Chi; Wang, Hsin-Wen; Chuang, Jui-Che; Fang, Yi-Qiao; Huang, Chieh-Cheng
Abstract: Ischemic stroke, and the consequent brain cell death, is a common cause of death and disability worldwide. Current treatments that primarily aim to relieve symptoms are relatively inefficient in achieving brain tissue regeneration and functional recovery, and thus novel therapeutic options are urgently needed. Although cell-based therapies have shown promise for treating the infarcted brain, a recurring challenge is the inadequate retention and engraftment of transplanted cells at the target tissue, thereby limiting the ultimate therapeutic efficacy. Here, we show that transplantation of preassembled three-dimensional (3D) spheroids of mesenchymal stem cells (MSCs) and vascular endothelial cells (ECs) results in significantly improved cell retention and survival compared with conventional mixed-cell suspensions. The transplanted 3D spheroids exhibit notable neuroprotective, proneurogenic, proangiogenic and anti-scarring potential as evidenced by clear extracellular matrix structure formation and paracrine factor expression and secretion; this ultimately results in increased structural and motor function recovery in the brain of an ischemic stroke mouse model. Therefore, transplantation of MSCs and ECs using the 3D cell spheroid configuration not only reduces cell loss during cell harvesting/administration but also enhances the resultant therapeutic benefit, thus providing important proof-of-concept for future clinical translation.